Block triangular preconditioner for static Maxwell equations - Wu, Shi-Liang; Huang, Ting-Zhu; Li, Liang (Computational & applied mathematics, 2011)
In this paper, we explore the block triangular preconditioning techniques applied to the iterative solution of the saddle point linear systems arising from the discretized Maxwell equations. Theoretical analysis shows that all the eigenvalues of the preconditioned matrix arestrongly clustered. Numerical experiments are given to demonstrate the efficiency of the presented preconditioner. Mathematical subject classification: 65F10.